2012
DOI: 10.1002/pssa.201200581
|View full text |Cite
|
Sign up to set email alerts
|

Grain size tuning of nanocrystalline chemical vapor deposited diamond by continuous electrical bias growth: Experimental and theoretical study

Abstract: In this work, a detailed structural and spectroscopic study of nanocrystalline diamond (NCD) thin films grown by a continuous bias assisted CVD growth technique is reported. This technique allows the tuning of grain size and phase purity in the deposited material. The crystalline properties of the films are characterized by SEM, TEM, EELS, and Raman spectroscopy. A clear improvement of the crystalline structure of the nanograined diamond film is observed for low negative bias voltages, while high bias voltages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 45 publications
3
42
0
Order By: Relevance
“…[21][22][23][24][25][26] The application of negative bias voltage in CH 4 / H 2 plasma attracts the positively charged species, such as H þ , CH 3 þ , CH þ and expels the electrons that markedly alter the plasma chemistry near the substrates. [21][22][23][24][25][26] Shigesato et al 48 found that negative biasing increased the concentration of atomic hydrogen in the CH 4 /H 2 plasma and proposed that this could cause preferential etching of sp 2 -bonded C. On the other hand, Robertson et al 49 proposed that ion subplantation due to applied negative bias causes deposition of nanocrystalline graphitic C, and that diamond nucleates where the graphitic planes are locally oriented perpendicular to the surface. Zhong et al 25 described that during negative bias in CH 4 /H 2 plasma, the diamond grains were formed easier than on graphitic phases, so the diamond grains grow rapidly covering the graphitic phases, minimizing the influence of the nucleation sites of the graphitic phases on the subsequent growth process of the diamond grains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24][25][26] The application of negative bias voltage in CH 4 / H 2 plasma attracts the positively charged species, such as H þ , CH 3 þ , CH þ and expels the electrons that markedly alter the plasma chemistry near the substrates. [21][22][23][24][25][26] Shigesato et al 48 found that negative biasing increased the concentration of atomic hydrogen in the CH 4 /H 2 plasma and proposed that this could cause preferential etching of sp 2 -bonded C. On the other hand, Robertson et al 49 proposed that ion subplantation due to applied negative bias causes deposition of nanocrystalline graphitic C, and that diamond nucleates where the graphitic planes are locally oriented perpendicular to the surface. Zhong et al 25 described that during negative bias in CH 4 /H 2 plasma, the diamond grains were formed easier than on graphitic phases, so the diamond grains grow rapidly covering the graphitic phases, minimizing the influence of the nucleation sites of the graphitic phases on the subsequent growth process of the diamond grains.…”
Section: Discussionmentioning
confidence: 99%
“…A few earlier reports [21][22][23][24][25] observed that the application of bias voltage in the CH 4 /H 2 plasma-based microwave plasma enhanced CVD (MPECVD) process not only facilitated the growth of diamond, but also efficiently reduced the size of the grains, resulting in diamond films with nanosized granular structure. In addition, Teng et al 26 reported the enhanced EFE behavior of bias-enhanced grown (BEG) nanocrystalline diamond (NCD) films using CH 4 CH 4 /H 2 plasma and the feasibility of bias enhanced growth of UNCD films using CH 4 /Ar plasma has not been reported yet.…”
Section: /Ar Plasma I Introductionmentioning
confidence: 99%
“…The MW PECVD diamond films are purer than the natural diamond ones, because the extrinsically impure elements will be excluded from the composition except some inevitable hydrogencarbon contaminations. To be different in the polycrystalline diamond films, the grain size in the NCD films is below 100 m μ [10][11][12]. It is expected that plenty of boundaries existing in the films influence the electronic and optical properties as well [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…They used Raman spectroscopy with different wavelengths and discussed the TPA decomposition at temperature lower than that for the film growth. In conclusion, the peak at 1150 cm -1 was attributed to the deformation mode of the CH x bond 26 . The X-ray diffraction patterns of the BDUND/PS electrodes are presented in Figure 5.…”
Section: Resultsmentioning
confidence: 81%